Enhancing the Quality of Indonesian Language Instruction for Elementary School Students Using Puzzle Media and the Know-Want-Learn Approach - Nikmatul Uliah (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
The purpose of this study was to improve student cooperation and learning outcomes of grade IV students of Elementary School 19 Buton Tengah. This type of research uses classroom action research with 28 students as subjects. The minimum competency criteria value in this school is 80. Research activities include planning, action, observation and reflection. Data collection uses observation and tests. The results of the study in cycle I, the percentage of learning completion was 64% with an average learning outcome score of 75.7. In cycle II, there was an increase, namely with a percentage of learning completion of 100% with an average learning outcome score of 87. From the assessment results, there were 5 groups that experienced an increase with 3 groups being very good at collaborating between students and 2 groups also being good at collaborating between students. So improving learning by using puzzle media has succeeded in improving learning outcomes and increasing activity between students to complete the tasks given.